The effect of company work discipline: Systematic literature review (Lighthouse Publishing, 2022)
This Systematic Literature Review collects some of the literature that discusses the influence of work discipline. Discipline is a tool commonly used to interact between management and employees so that it can change behavior and become an effort by company leaders to increase awareness and willingness of employees to comply with company rules and applicable social norms. This research aims to explore the literature related to Work Discipline. This research was compiled using Preferred Reporting Items for Systematic Review and Meta-Analysis. The data collection method uses Population, Intervention, Comparison & Outcome (PICO) and data inclusion. Some of the literature obtained was 40 from two sources, Garba Digital Referrals (Garuda) and Scopus with Publish or Perish software tools. Then a screening was carried out, and as many as 30 works of literature were obtained. The results show that most of the literature shows the results of work discipline affecting the dependent variable of each literature (Performance, Productivity and Employee Achievement). Nineteen works of literature on influence performance, three works of literature on productivity and three works of literature on employee performance. On the other hand, one piece of literature makes work discipline a moderating variable. This result can be used as a reference and consideration for policymakers (companies) to pay attention to work discipline.